Ciliary neurotrophic factor prevents degeneration of adult rat substantia nigra dopaminergic neurons in vivo. - Hagg, T (1993)
We have investigated the neuroprotective effects of recombinant human ciliary neurotrophic factor (CNTF) for injured dopaminergic neurons of the adult rat substantia nigra compacta. Fourteen days after a unilateral transection of the nigrostriatal pathway two-thirds of the neurons (identified by retrograde labeling) had degenerated. In sharp contrast, 73% (a few cases, > 90%) of this cell loss was prevented by continuous infusion of CNTF close to the injured neurons. However, CNTF did not prevent the disappearance of the transmitter-synthesizing enzyme tyrosine hydroxylase. Thus, CNTF has potent neurotrophic effects for injured adult rat dopaminergic substantia nigra neurons, whose degeneration plays a major causative role in Parkinson disease.